Bitter gourd-shaped particle-bacterial cellulose composite membrane as well as preparation method and application thereof

Through the preparation of bitter melon-like particles-bacterial cellulose composite film, the problem of high pressure and high temperature of the existing biomass carbon material preparation methods is solved, and a low-cost and low-energy consumption solar interface evaporator is realized, which significantly improves water evaporation performance and stability , which has promoted the application of solar-powered seawater desalination technology.

CN119281136APending Publication Date: 2025-01-10UNIV OF CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411800531.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing biomass carbon material preparation methods for solar interface evaporation require high pressure and high temperature conditions, resulting in high energy consumption and high cost, limiting its practical application.

Method used

The preparation method of bitter melon-like particles-bacterial cellulose composite film is adopted. By pulverizing sawdust, freeze-drying, sulfuric acid treatment and bacterial cellulose, a low-cost, low-energy consumption photothermal conversion material is formed, which is used in solar interface evaporators.

Benefits of technology

It significantly reduces material costs, improves light absorption capacity and water evaporation performance, and the BMPs-BC evaporator exhibits excellent stability and salt resistance, achieving low energy consumption and efficient seawater desalination.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119281136A_ABST
    Figure CN119281136A_ABST
Patent Text Reader

Abstract

The invention discloses a balsam pear-shaped particle-bacterial cellulose composite membrane as well as a preparation method and application thereof. According to the method, the waste sawdust is converted into bitter gourd-shaped particles (BMPs) with rich carbon dots (CDs) and carbon nanospheres (CNSs) on the surface through simple sulfuric acid treatment. The composite material (BMPs-BC) with excellent light absorption capacity (94.6%) and efficient solar driven water evaporation performance (3.53 kg m <-2 > h <-1 >) is prepared by compounding BMPs with bacterial cellulose (BC). Compared with the traditional direct high-temperature carbonization and hydrothermal carbonization methods, the sulfuric acid treatment method adopted by the invention avoids the use of high-temperature and high-pressure conditions. The sawdust is used as the raw material, so that the problem of waste treatment is effectively solved, and the material cost is remarkably reduced. The invention provides a new strategy for preparing a sustainable, efficient and low-cost solar-driven water evaporator by using waste biomass materials, and provides important technical support for relieving the problem of global water resource shortage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the fields of material technology research and water treatment technology, and in particular to a bitter melon-shaped particle-bacterial cellulose composite membrane and a preparation method and application thereof. Background Art

[0002] The continued growth of the global population, the acceleration of industrialization, and the drought caused by climate change have further increased the demand for freshwater resources. In this context, seawater desalination technology has become increasingly important. Traditional seawater desalination methods mainly include distillation and membrane separation. However, high energy consumption and high costs limit the further popularization of these technologies. Therefore, there is an urgent need to develop more sustainable, cost-effective alternatives.

[0003] Solar-driven desalination technology has become a solution that has attracted much attention due to its low cost and green environmental protection characteristics. Among them, the interfacial evaporation technology based on solar energy is considered to be a desalination technology with great application prospects due to its simple equipment and high photothermal conversion efficiency. The core of the solar interfacial evaporation system lies in the photothermal conversion material located at the water-air interface, and its performance directly determines the evaporation efficiency of the device. Currently, the commonly used photothermal conversion materials include metal nanomaterials, semiconductor materials, polymer materials and carbon-based materials. Among them, carbon-based materials have more practical application value due to their wide range of light absorption, low cost and strong stability. The carbon materials used in solar interfacial evaporators mainly include carbon nanotubes, graphene and biomass carbon. Among them, biomass carbon is unmatched by other carbon materials in terms of cost because its raw material biomass has the advantages of large reserves, renewability and low cost. However, the biomass carbon currently used for solar interfacial evaporation is mostly prepared by direct carbonization and hydrothermal carbonization methods. These methods usually require high pressure and high temperature processing conditions, which not only rely on expensive equipment but also cause great energy consumption. Therefore, the development of a low-cost, low-energy consumption, high-performance photothermal conversion material and its preparation method is of great significance for promoting the practical application of solar-driven interfacial evaporation technology. Summary of the invention

[0004] The shortcomings of the existing preparation methods of biomass carbon materials for solar interface evaporation hinder their practical application. The purpose of the present invention is to provide a low-cost, low-energy consumption, high-performance preparation method of biomass carbon materials, and use it for solar interface evaporation.

[0005] The above-mentioned object of the present invention is achieved by the following technical solutions:

[0006] A bitter melon-like microparticle-bacterial cellulose composite membrane is prepared by mixing bitter melon-like microparticles and bacterial cellulose in a ratio of 7:3, and then vacuum filtering to obtain a bitter melon-like microparticle-bacterial cellulose composite membrane (BMPs-BC composite membrane).

[0007] A method for preparing a bitter melon-shaped particle-bacterial cellulose composite film comprises the following steps:

[0008] Step 1, crush the sawdust through a powder machine;

[0009] Step 2, sieving the powder of step 1 through a sieve;

[0010] Step 3, dispersing the sieved sawdust in step 2 in deionized water to prepare a suspension;

[0011] Step 4, homogenizing the suspension of step 3;

[0012] Step 5, freeze-drying the sawdust suspension in step 4 to obtain dry sawdust powder;

[0013] Step 6, preparing concentrated sulfuric acid solution;

[0014] Step 7, heating the concentrated sulfuric acid solution of step 6;

[0015] Step 8, adding the sawdust powder of step 5 to the concentrated sulfuric acid of step 7 under stirring conditions to react;

[0016] Step 9, adding the reaction product of step 8 into deionized water to terminate the reaction;

[0017] Step 10, filtering the mixed solution of step 9 and collecting the solid product;

[0018] Step 11, washing the solid product of step 10 with deionized water until the filtrate is neutral, collecting the black solid product, i.e., bitter melon-like particles, named BMPs;

[0019] Step 12, dispersing the black solid product of step 11 into deionized water to obtain a BMPs suspension;

[0020] Step 13: Mix the BMPs suspension obtained in step 12 with bacterial cellulose (BC) at a mass ratio of 7:3, and then perform vacuum filtration to obtain a BMPs-BC composite membrane.

[0021] In the above technical solution, in step 2, the mesh size of the sieve is 100 meshes, and the size of the sawdust is less than 400 µm.

[0022] In the above technical solution, in step 3, the mass fraction of the sawdust suspension is 0.1% - 10%.

[0023] In the above technical solution, in step 4, the homogenization method is to use a high-pressure homogenizer to homogenize at a pressure of 600 MPa for 20 minutes.

[0024] In the above technical solution, in step 6, the concentration of the concentrated sulfuric acid solution is 78%.

[0025] In the above technical solution, in step 7, the heating temperature is 80°C.

[0026] In the above technical solution, in step 8, the reaction duration is 12 hours.

[0027] In the above technical solution, in step 9, the volume of deionized water is 10 times that of the reaction product.

[0028] A bitter melon-shaped particle-bacterial cellulose composite film or a method for preparing a bitter melon-shaped particle-bacterial cellulose composite film is used in solar interface seawater desalination.

[0029] Beneficial effects:

[0030] Compared with the existing technology, the method of the present invention avoids high pressure and high temperature conditions. Using waste sawdust as raw material not only effectively solves the problem of waste disposal, but also significantly reduces the material cost. On the other hand, using BC as a composite material increases the evaporation enthalpy of water in BMPs-BC from 2409.6 J g -1 Reduced to 1003.4 J g -1 The constructed BMPs-BC evaporator has excellent light absorption capacity (94.6%) and efficient solar-driven water evaporation performance (3.53 kg m -2 h -1 The BMPs-BC evaporator also exhibited excellent stability and salt resistance. There was no salt deposition on the surface after continuous operation for 24 hours in real seawater, and the water evaporation performance remained stable. In the outdoor long-term test, the maximum water evaporation rate of the BMPs-BC evaporator array was 2.86 kg m -2 h -1 , the daily cumulative water production reaches 15.9 kg -1 m -2 This research greatly reduces the cost of solar-driven water evaporators and is of great significance for promoting the practical application of solar-driven interfacial water evaporation technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a scanning electron microscope (SEM) image of the original sawdust.

[0032] Figure 2 The SEM image of the sawdust after homogenization.

[0033] Figure 3These are scanning electron microscope (SEM) images of bitter melon-like microparticles (BMPs) and actual photos of bitter melon.

[0034] Figure 4 This is a Transform Electron Microscope (TEM) image of bitter melon-shaped BMPs particles.

[0035] Figure 5 TEM image of carbon dots.

[0036] Figure 6 This is the SEM image of bacterial cellulose.

[0037] Figure 7 This is the SEM image of BMPs and bacterial cellulose composite membrane BMPs-BC.

[0038] Figure 8 : Fluorescence emission spectra of carbon dots at different excitation wavelengths.

[0039] Fig. 9 X-ray diffraction patterns of sawdust, carbon dots and BMPs.

[0040] Fig.10 Raman spectra of carbon dots and BMPs in the range of 1000 - 1800 nm.

[0041] Fig.11 Raman spectra of sawdust and BMPs in the range of 2600 - 3200 nm.

[0042] Fig.12 Fourier transform infrared spectra of sawdust and BMPs.

[0043] Fig.13 X-ray photoelectron spectroscopy (XPS) spectra of sawdust and BMPs.

[0044] Fig.14 High-resolution C1s spectra of sawdust and BMPs.

[0045] Fig.15 High-resolution O1s spectra of sawdust and BMPs.

[0046] Fig.16 High-resolution S2p spectrum of BMPs.

[0047] Fig.17 This is the Differential Scanning Calorimeter (DSC) test result of BMPs-BC composite membrane.

[0048] Fig.18UV-visible-near-infrared absorption spectrum of BMPs-BC composite membrane in the wavelength range of 300 - 2000 nm.

[0049] Fig.19 Schematic diagram of the indoor test experimental setup for BMPs-BC evaporator.

[0050] Fig. 20 is the water evaporation rate of the BMPs-BC evaporator under one sun intensity.

[0051] Fig.21 This is a physical picture of the BMPs-BC evaporator outdoor test device and its status after 30 minutes of operation.

[0052] Fig. 22 Outdoor testing of water evaporation rate and cumulative freshwater production weight for the BMPs-BC evaporator.

[0053] Fig.23 is the solar radiation intensity during the outdoor test of BMPs-BC evaporator.

[0054] Fig.24 Temperature and humidity during outdoor testing of the BMPs-BC evaporator. DETAILED DESCRIPTION

[0055] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. However, the following embodiments are limited to explaining the present invention, and the protection scope of the present invention should include the entire contents of the claims, and through the description of the following embodiments, those skilled in the art can fully implement the entire contents of the claims of the present invention.

[0056] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content recorded in the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope limited by the present invention. The raw materials can all be obtained from public commercial channels if not otherwise specified.

[0057] Example 1

[0058] (1) Sawdust pretreatment: First, the sawdust was further crushed by a powder mill and sieved through a 100-mesh sieve to obtain sawdust less than 400 µm. Then, 1 g of the sieved sawdust was dispersed in 100 mL of deionized water and treated with a high-pressure homogenizer at pressures of 100, 200, 400, 600, 800, and 1000 MPa for 10 min, respectively, to obtain a more uniformly dispersed sawdust suspension. Subsequently, the sawdust suspension was freeze-dried to obtain dry sawdust powder.

[0059] (2) Preparation of bitter melon-like microparticles: Sulfuric acid (95%-98%) and deionized water were mixed in a volume ratio of 2:1 to prepare a sulfuric acid solution. 50 mL of the sulfuric acid solution was heated to 80°C, and 0.5 g of sawdust treated by a high-pressure homogenizer was added to the 50 mL of the sulfuric acid solution under continuous stirring, and the mixture was reacted at 80°C for 4 hours. After the reaction was completed, the product was added to 10 times the volume of deionized water to reduce the acidity and terminate the reaction. Then, the mixture was filtered to collect the solid product, and the solid product was washed several times with 200 mL of deionized water until the filtrate was neutral. The final product was bitter melon-like microparticles (BMPs). The BMPs were dispersed in deionized water to obtain a suspension of BMPs (20 mg / g).

[0060] Example 2

[0061] (1) Sawdust pretreatment: First, the sawdust was further crushed by a powder mill and sieved through a 100-mesh sieve to obtain sawdust less than 400 µm. Then, 1 g of the sieved sawdust was dispersed in 100 mL of deionized water and treated with a high-pressure homogenizer at pressures of 100, 200, 400, 600, 800, and 1000 MPa for 10 min, respectively, to obtain a more uniformly dispersed sawdust suspension. Subsequently, the sawdust suspension was freeze-dried to obtain dry sawdust powder.

[0062] (2) Preparation of bitter melon-like microparticles: Sulfuric acid (95%-98%) and deionized water were mixed in a volume ratio of 2:1 to prepare a sulfuric acid solution. 50 mL of the sulfuric acid solution was heated to 80°C, and 0.5 g of sawdust treated by a high-pressure homogenizer was added to the 50 mL of the sulfuric acid solution under continuous stirring, and the mixture was reacted at 80°C for 8 hours. After the reaction was completed, the product was added to 10 times the volume of deionized water to reduce the acidity and terminate the reaction. Then, the mixture was filtered to collect the solid product, and the solid product was washed several times with 200 mL of deionized water until the filtrate was neutral. The final product was bitter melon-like microparticles (BMPs). The BMPs were dispersed in deionized water to obtain a suspension of BMPs (20 mg / g).

[0063] Example 3

[0064] (1) Sawdust pretreatment: First, the sawdust was further crushed by a powder mill and sieved through a 100-mesh sieve to obtain sawdust less than 400 µm. Then, 1 g of the sieved sawdust was dispersed in 100 mL of deionized water and treated with a high-pressure homogenizer at pressures of 100, 200, 400, 600, 800, and 1000 MPa for 10 min, respectively, to obtain a more uniformly dispersed sawdust suspension. Subsequently, the sawdust suspension was freeze-dried to obtain dry sawdust powder.

[0065] (2) Preparation of bitter melon-like microparticles: Sulfuric acid (95%-98%) and deionized water were mixed in a volume ratio of 2:1 to prepare a sulfuric acid solution. 50 mL of the sulfuric acid solution was heated to 80°C, and 0.5 g of sawdust treated by a high-pressure homogenizer was added to the 50 mL of the sulfuric acid solution under continuous stirring, and the mixture was reacted at 80°C for 12 hours. After the reaction was completed, the product was added to 10 times the volume of deionized water to reduce the acidity and terminate the reaction. Then, the mixture was filtered to collect the solid product, and the solid product was washed several times with 200 mL of deionized water until the filtrate was neutral. The final product was bitter melon-like microparticles (BMPs). The BMPs were dispersed in deionized water to obtain a dispersion of BMPs (20 mg / g).

[0066] Example 4

[0067] (1) Sawdust pretreatment: First, the sawdust was further crushed by a powder mill and sieved through a 100-mesh sieve to obtain sawdust less than 400 µm. Then, 1 g of the sieved sawdust was dispersed in 100 mL of deionized water and treated with a high-pressure homogenizer at pressures of 100, 200, 400, 600, 800, and 1000 MPa for 10 min, respectively, to obtain a more uniformly dispersed sawdust suspension. Subsequently, the sawdust suspension was freeze-dried to obtain dry sawdust powder.

[0068] (2) Preparation of bitter melon-like microparticles: Sulfuric acid (95%-98%) and deionized water were mixed in a volume ratio of 2:1 to prepare a sulfuric acid solution. 50 mL of the sulfuric acid solution was heated to 80°C, and 0.5 g of sawdust treated by a high-pressure homogenizer was added to the 50 mL of the sulfuric acid solution under continuous stirring, and the mixture was reacted at 80°C for 12 hours. After the reaction was completed, the product was added to 10 times the volume of deionized water to reduce the acidity and terminate the reaction. Then, the mixture was filtered to collect the solid product, and the solid product was washed several times with 200 mL of deionized water until the filtrate was neutral. The final product was bitter melon-like microparticles (BMPs). The BMPs were dispersed in deionized water to obtain a dispersion of BMPs (20 mg / g).

[0069] (3) Water evaporation performance test: BMPs (14 mg) and bacterial cellulose (6 mg) were mixed, and then the mixed suspension was filtered to obtain the BMPs-BC composite membrane. To determine the evaporation rate of water, a glass beaker (diameter ≈ 60 mm, height 10 cm) was used to store water, and an 8 mm thick polyethylene foam board was used as an insulation layer. A piece of filter paper was placed on the upper surface of the polyethylene foam to ensure direct contact with the water to facilitate water transport. Subsequently, the BMPs-BC composite membrane was placed on the filter paper. The indoor solar evaporator test was carried out using a solar simulator with an output solar flux of 1 kW m -2(Equivalent to the radiation intensity of one sun). Before each test, the light intensity was calibrated using a thermal power sensor.

[0070] In the outdoor experiments, a larger glass container (10 cm long, 6 cm wide, and 10 cm high) was used to store water, and an 8 mm thick polyethylene foam board was used as a thermal insulation layer. A filter paper was placed on the upper surface of the polyethylene foam to ensure direct contact with the water to facilitate water transport. Subsequently, 20 BMPs-BC composite membranes were arranged on the filter paper in a 5×8 array. Solar radiation, temperature, and humidity during the outdoor test were recorded by a portable weather station.

[0071] The morphology and structure of the original sawdust, homogenized sawdust, bitter melon-shaped particles, and BMPs-BC composite membranes in Examples 1-4 were characterized, and the performance of the constructed evaporator was tested.

[0072] 1. Morphology test

[0073] Scanning electron microscope (SEM) images show that the length and width of the original sawdust particles are approximately 50-250 µm and 14-57 µm, respectively ( Figure 1 After high-pressure homogenization, the length and width of the particle size were significantly reduced to approximately 8-36 µm and 0.12-1.34 µm, respectively, and a large number of wood chip fragments with a length of less than 1 µm were produced ( Figure 2 After sulfuric acid treatment, the obtained particles have a structure similar to that of bitter melon (BMPs), with a large number of nanospheres formed on the surface of the rod-shaped particles ( Figure 3 ), with an average diameter of 46.02±6.34nm. Transmission electron microscopy (TEM) images showed that there were nanospheres and abundant carbon dots on the surface of BMPs ( Figure 4 The diameters of these carbon dots range from 1.3 to 5.8 nm, with an average diameter of 3.5 nm ( Figure 5 ). SEM shows that bacterial cellulose (BC) film is a three-dimensional interconnected porous nanofiber network ( Figure 6 ), with diameters ranging from 10 to 100 nm. The surface and cross-sectional morphologies of the BMPs-BC composite membranes are shown in Figure 7 As shown, BC is coated on the surface of BMPs and connected to each other, and these interconnected structures are conducive to the transport of water molecules.

[0074] 2. Chemical structure characterization

[0075] The fluorescence emission spectrum of carbon dots is shown in Figure 8 As shown in Figure 2, the emission wavelength shifts with the excitation wavelength. The crystal structure characteristics of carbon dots and BMPs were studied by XRD analysis. Fig. 9As shown, carbon dots show a broad diffraction peak at 22.9°, which is a typical feature of amorphous carbon. BMPs show characteristic cellulose I diffraction peaks at 2θ = 15.3° (110) and 2θ = 22.3° (200), indicating that the internal cellulose structure is preserved. It is worth noting that the peak at 22.3° of BMPs is broadened compared to sawdust, mainly because BMPs are carbonized. Fig.10 As shown in Figure 2, the CDs curve is above the BMPs curve. The Raman spectrum shows that the sawdust is successfully carbonized. In addition, a carbonization peak at 2940 cm-1 is observed in the Raman spectrum of BMPs. -1 The cellulose CH stretching vibration at Fig.11 ), further confirming that the cellulose component was preserved. Fourier transform infrared spectroscopy and X-ray electron spectroscopy analysis showed that there were sulfonic acid groups in BMPs ( Fig.12 , Fig.13 , Fig.14 , Fig.15 and Fig.16 ).

[0076] 3. Analysis of BMPs-BC evaporation performance

[0077] like Fig.17 As shown in Figure 2, DSC shows that the evaporation enthalpy of water in the BMPs-BC composite membrane is significantly lower than that of pure water. Fig.18 As shown in FIG. 1 , the UV-visible-near infrared absorption spectrum shows that increasing the proportion of BMPs in the BMPs-BC composite film can improve the light absorption capacity, and the maximum light absorption rate is 95.6%. Then, this embodiment uses Fig.19 The system shown evaluates the evaporation performance of the BMPs-BC composite membrane. In this evaporation system, a glass beaker is used to store water, the BMPs-BC composite membrane is used as a light-to-heat conversion layer, a polyethylene foam board is used as an insulation layer, and a filter paper is placed between the polyethylene foam and the BMPs-BC composite membrane in contact with the water to transfer water. The evaporation system was tested using a solar simulator, and its water production rate was evaluated by monitoring its mass reduction rate. Under single sunlight irradiation, the evaporation rate of the BMPs-BC evaporator first increased and then decreased with the increase in the proportion of BMPs. When the weight ratio of BMPs to BC nanofibers was 7:3, the evaporation rate reached a maximum value of 3.53 kg m -2 h -1 ( Fig. 20 ). This embodiment uses a test device to evaluate the evaporation performance of BMPs-BC outdoors. In the test device, a sealing device made of acrylic plate is used to collect water. The evaporator array consists of 20 BMPs-BC composite membranes with a diameter of 1.5 cm, which are placed in the water collection device. The water production is tested by detecting the quality of fresh water in the water collection device. Fig.21As shown in the figure, a large amount of fresh water condensed on the evaporator surface after the evaporator was operated for 30 minutes. The maximum water production rate during the test was 2.86 kg m -2 h -1 The cumulative amount of fresh water obtained from 9:00 to 18:00 (9 hours) was 15.9 kg m -2 ( Fig. 22 ). The solar radiation intensity, temperature and humidity during the test are as follows: Fig.23 and Fig.24 shown.

[0078] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A bitter melon-shaped microparticle-bacterial cellulose composite film, characterized in that: The bitter melon-like particles and bacterial cellulose were mixed in a ratio of 7:3, and then vacuum filtered to obtain a bitter melon-like particle-bacterial cellulose composite membrane.

2. A method for preparing a bitter melon-shaped particle-bacterial cellulose composite film, characterized in that: The steps include: Step 1, crush the sawdust through a powder machine; Step 2, sieving the powder of step 1 through a sieve; Step 3, dispersing the sieved sawdust in step 2 in deionized water to prepare a suspension; Step 4, homogenizing the suspension of step 3; Step 5, freeze-drying the sawdust suspension in step 4 to obtain dry sawdust powder; Step 6, preparing concentrated sulfuric acid solution; Step 7, heating the concentrated sulfuric acid solution of step 6; Step 8, adding the sawdust powder of step 5 to the concentrated sulfuric acid of step 7 under stirring conditions to react; Step 9, adding the reaction product of step 8 into deionized water to terminate the reaction; Step 10, filtering the mixed solution of step 9 and collecting the solid product; Step 11, washing the solid product of step 10 with deionized water until the filtrate is neutral, collecting the black solid product, i.e., bitter melon-like particles, named BMPs; Step 12, dispersing the black solid product of step 11 into deionized water to obtain a BMPs suspension; Step 13: Mix the BMPs suspension obtained in step 12 with bacterial cellulose in a mass ratio of 7:3, and then perform vacuum filtration to obtain a bitter melon-shaped particle-bacterial cellulose composite membrane.

3. The method for preparing a bitter melon-shaped particle-bacterial cellulose composite film according to claim 2, characterized in that: In step 2, the mesh size of the screen is 100 mesh and the size of the sawdust is less than 400 µm.

4. The method for preparing a bitter melon-shaped particle-bacterial cellulose composite film according to claim 2, characterized in that: In step 3, the mass fraction of the sawdust suspension is 0.1% - 10%.

5. The method for preparing a bitter melon-shaped particle-bacterial cellulose composite film according to claim 2, characterized in that: In step 4, the homogenization method is to use a high pressure homogenizer at a pressure of 600 MPa for 20 minutes.

6. The method for preparing a bitter melon-shaped particle-bacterial cellulose composite film according to claim 2, characterized in that: In step 6, the concentration of the concentrated sulfuric acid solution is 78%.

7. The method for preparing a bitter melon-shaped particle-bacterial cellulose composite film according to claim 2, characterized in that: In step 7, the heating temperature is 80°C.

8. The method for preparing a bitter melon-shaped particle-bacterial cellulose composite film according to claim 2, characterized in that: In step 8, the duration of the reaction is 12 hours.

9. The method for preparing a bitter melon-shaped particle-bacterial cellulose composite film according to claim 2, characterized in that: In step 9, the volume of deionized water is 10 times the volume of the reaction suspension.

10. Use of the bitter melon-shaped particle-bacterial cellulose composite film according to claim 1 or the method for preparing the bitter melon-shaped particle-bacterial cellulose composite film according to any one of claims 2 to 9 in solar interfacial seawater desalination.